PENGELOLAAN SUMBER BELAJAR BERBASIS TIK DI MA UNGGULAN AL-IMDAD YOGYAKARTA : Management Of Ict-Based Learning Resources At MA Unggul Al Imdad Yogyakarta - Sari, Pusvyta; Murod, Ahmad (PUSAT PUBLIKASI ILMIAH SEKOLAH TINGGI AGAMA ISLAM (STAI) AL-YASINI PASURUAN, 2024)
The development of information and communication technology (ICT) is very fast. Everyone who has internet connection can access a lot of information quickly. ICT makes learning resources widespread and varied, someone can learn knowledge and skills and experiences from internet. However, the negative side is worrying, for example, there are fake news, hate speech and bad content. Some boarding school forbidding to use internet for protect students from negativity. This research wants to know how ICT-based learning resources are managed at the Unggulan Al Imdad Yogyakarta MA, which is based on Islamic boarding school, does not prohibit the internet from being a learning resource. This is qualitative research. Data mining methods are carried out through interviews, observation and documentation. The results of the research show that the management of information and communication technology-based learning resources at the MA Unggulan Al Imdad is carried out through a process of planning, procurement, utilization as well as supervision, inventory storage and deletion and arrangement. Management of ICT-based learning resources requires mutual awareness and responsibility between managers and users. Before making it happen, managing ICT-based learning resources needs to consider its suitability with the madrasah's vision, mission and goals. So, its implementation does not deviate from the vision, mission and goals. Next, it is necessary to carry out follow-up actions that can maximize the use of available ICT-based learning resources to improve the quality of learning and school. For example, increasing knowledge and skills of teachers and students is not only in accessing learning resources, but can also produce creative and innovative digital content.